Effectiveness of Security in Software Defined Networks - Devi, B. Parvathi; Vallinayagi, V (International Journal of Computer Sciences and Engineering, 2025)
Software Defined Networks are the new standard in networking. ONF [Open Networking Foundation] contributes a high level architecture for SDN. It has three layers, they are Infrastructure layer, control layer and application layer.[1] From the ONF we gets a well-defined definition for SDN which is as follows, “In the SDN architecture, the control and data planes are decoupled, network intelligence and state are logically centralized, and the underlying network infrastructure is abstracted from the applications” [2]. The network security in the SDN architecture is improved by the centralized control over the network and controls the traffic in run time. This paper analyse and produce the importance and effectives of the SDN architecture for future networking.